A pilot study of serotonergic modulation after long‐term administration of oxytocin in autism spectrum disorder. Issue 5 (7th March 2017) - Hirosawa, Tetsu; Kikuchi, Mitsuru; Ouchi, Yasuomi; Takahashi, Tetsuya; Yoshimura, Yuko; Kosaka, Hirotaka; Furutani, Naoki; Hiraishi, Hirotoshi; Fukai, Mina; Yokokura, Masamichi; Yoshikawa, Etsuji; Bunai, Tomoyasu; et al.
Abstract : Oxytocin (OT) and the serotonergic system putatively play important roles in autism spectrum disorder (ASD) etiology and symptoms, but no direct neurobiological evidence exists for long‐term OT administration effects on the brain's serotonergic system. This pilot study examined 10 male participants with ASD who were administered OT intranasally for 8–10 weeks in an open‐label, single‐arm, nonrandomized, and uncontrolled manner. Positron emission tomography (PET) with a radiotracer ( 11 C)−3‐amino‐4‐(2‐[(dimethylamino)methyl]phenylthio)benzonitrile ( 11 C‐DASB) was used before and after OT treatment. The binding potential of serotonin transporter ( 11 C‐DASB BPND ) was then estimated. The main outcome measures were changes in 11 C‐DASB BPND and their correlation with changes in symptoms. ASD participants showed significantly elevated 11 C‐DASB BPND in the left inferior frontal gyrus extending to the left middle frontal gyrus. No significant correlation was found between the change in any clinical symptom and the change in 11 C‐DASB BPND . This report of a pilot study is the first describing long‐term effects of OT on the brain's serotonin system in ASD. Additional randomized controlled studies must be conducted to confirm whether activation of the serotonergic system contributes to the prosocial effect of OT in people with ASD. Autism Res 2017, 10: 821–828 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.